(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
درست الصفات المظهرية المميزة لعزلات الفطر Ascochyta fabae مجموعة من محافظات سورية مختلفة ( حلب، إدلب، حماه، درعا، اللاذقية، طرطوس). أظهرت النتائج وجود اختلافات كبيرة ما بين العزلات من حيث لون المستعمرة، طبيعة الميسليوم، معدل التبوغ، قطر المستعمرة ومعدل النمو. ووجدت اختلافات ما بين المكررات التابعة للعزلة ذاتها وصلت إلى 18%. ولم يكن بالإمكان تصنيف العزلات في مجموعات متجانسة تبعاً للأصل الجغرافي أو العضو النباتي الذي أخذت منه. وأظهرت دراسة الأنماط المرضّية (Pathotypes)، باستخدام سبعة أصناف تفريقية، لـ 40 عزلة بينها ثلاثون كانت قد جمعت من حقل واحد في محافظة إدلب، وعشرعزلات من محافظات سورية أخرى، وبينت الدراسة وجود ثمانية أنماط مرضية من بينها ستة أمكن تمييزها من حقل واحد. ولم يظهر التحليل العنقودي وجود ارتباط بين العزلات التابعة للنمط المرضي ذاته من حيث صفاتها المورفولوجّية. A Morphological characterization is carried out on Syrian isolates of Ascochyta fabae collected from different Syrian governorates (Aleppo, Idleb, Hama, Lattakia, Tartous). Results reveal differences between isolates in colony color, mycelium texture, sporulation, colony diameter, and growth rate. 18% of single spore isolates show differences in replicates. It is not possible to classify isolates according to their geographical origin or the part collected from it. The patho-types of 30 isolates, taken from the same field (in Idleb), and 10 others taken from different Syrian governorates reveal the presence of 8 pathotypes, 6 of which are from one field. According to cluster analysis results, no correlation could be traced between isolates belonging to the same pathotype and their morphological properties.